ISAAC: a meta- cad system for virtual environments - Mine, Mark R (Computer aided design, 1997)
This paper presents a description of ISAAC; the Immersive Simulation Animation And Construction program designed and built at the University of North Carolina at Chapel Hill (UNC-CH). ISAAC is a scene composition application used for the interactive construction of virtual worlds. In ISAAC you work directly in a virtual environment; you position, orient and scale objects using direct and indirect manipulation techniques. ISAAC stores object configurations in ASCII files that it uses to recreate scenes at a later date for further manipulation and interactive exploration. ISAAC is not a modeling program; you create worlds by manipulating pre-generated three-dimensional models (which can come from sources such as computer-aided design programs or three-dimensional scanning devices). ISAAC was designed to overcome some of the limitations of working in a virtual environment and to take advantage of the natural and intuitive forms of interaction available in a virtual world.